(untitled) (Indian Journal of Chemistry (IJC), 2026)
A cobalt(II) coordination polymer of 2,6-pyridinedicarboxylic (2,6-pydc) and 4,4′-trimethylenedipyridine (4,4′-TMDP) has been resynthesized by new synthetic method. The polymer is then characterized through single crystal XRD (SC-XRD) analysis. Variety of other techniques such as elemental analysis, TGA, fluorescence spectroscopy, UV-Vis spectroscopy, FTIR spectroscopy and magnetic study have been employed for further characterization. This coordination polymer has been explored as a catalyst for degradation of methyl orange (MO) and congo red (CR) in an aqueous medium with the reducing agent sodium borohydride (NaBH4) under dark. Surprisingly, it is observed 96.41% and 97.22% degradation of MO and CR dyes within 8 and 10 minutes with rate constants 0.491min-1 and 0.264min-1 respectively.